2019
DOI: 10.3390/ma12091522
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Thermal Conductivity of Epoxy-Carbon Filler Composites Processed by Calendaring

Abstract: Electrical and thermal conductivity of composites which contain carbon-based fillers in an epoxy matrix were investigated. The fillers were dispersed in the liquid matrix by using three roll mill equipment. The filler/matrix mixture was cast in a mold and then cured, thus obtaining composite specimens. Multiwall carbon nanotubes, graphene-like nanoplatelets, and graphite were used as fillers and their effect on conductivity was investigated. Electrical and thermal conductivity were measured at different filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Induced shearing via the calandering method is also responsible for aligning CNTs as previously reported [4,40,[44][45][46]. When the fillers align in one direction, a continuous network of conductive element is formed as confirmed in number of previous studies [40,44,46]. An increase in the order of magnitude (i.e.…”
Section: Novel Carbyne Filled Carbon Nanotube -Polymer Nanocompositessupporting
confidence: 70%
“…Induced shearing via the calandering method is also responsible for aligning CNTs as previously reported [4,40,[44][45][46]. When the fillers align in one direction, a continuous network of conductive element is formed as confirmed in number of previous studies [40,44,46]. An increase in the order of magnitude (i.e.…”
Section: Novel Carbyne Filled Carbon Nanotube -Polymer Nanocompositessupporting
confidence: 70%
“…It was reported that both electrical conductivity and tensile strength were signicantly higher for samples with MWCNT of higher aspect ratio (length/ diameter). Caradonna et al, 16 have dispersed MWCNT and graphene platelets of different aspect ratios into the epoxy matrix by calendaring technique and made nano-composites. Results have shown improvement in the electrical and thermal conductivity of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…), ceramic (alumina [8,9], silicon carbide [10,11], boron nitride [9,12], halloysite nanotubes [13] etc.) or carbonaceous (single- [14] or multi-walled [15][16][17] carbon nanotubes [18], graphene [6,15,16,[18][19][20], carbon black [18,21,22], graphite [11,15,18]) fillers.…”
Section: Introductionmentioning
confidence: 99%